Ceratopogonidae from Costa Rica (Diptera). - Macfie, John William Scott (Contributions to Entomology = Beiträge zur Entomologie, 1953)
Nomenclatural Actscostaricae Macfie, 1953 (Atrichopogon), spec. n.didymothecae Macfie, 1953 (Atrichopogon), spec. n.lacajae Macfie, 1953 (Atrichopogon), spec. n.pachycnemus Macfie, 1953 (Atrichopogon), spec. n.utricularius Macfie, 1953 (Atrichopogon), spec. n.philotherma Macfie, 1953 (Dasyhelea), spec. n.pyrsonota Macfie, 1953 (Dasyhelea), spec. n.